Closing the hydrogen cycle with the couple sodium borohydride-methanol, via the formation of sodium tetramethoxyborate and sodium metaborate - Aydin, Kubra; Kulakli, Busra N.; Filiz, Bilge Coskuner; Alligier, Damien; Demirci, Umit B.; Figen, Aysel Kanturk (WILEY, 2020)
Methanolysis of sodium borohydride (NaBH4) is one of the methods efficient enough to release, on demand, the hydrogen stored in the hydride as well as in 4 equiv of methanol (CH3OH). It is generally reported that, in methanolysis, sodium tetramethoxyborate (NaB(OCH3)(4)) forms as single component of the spent fuel. It is, however, necessary to clearly investigate some critical aspects related to it. We first focused on the methanolysis reaction where NaBH(4)was reacted with 2, 4, 8, 16, or 32 equiv of CH3OH. With 2 equiv of CH3OH, the conversion of NaBH(4)is not complete. With 4 to 32 equiv of CH3OH, NaBH(4)is totally methanolized (conversion of 100%). The best conditions are those involving 4 equiv of CH3OH as they offer the highest effective gravimetric hydrogen storage capacity with 4.8 wt%, an attractive H(2)generation rate with 331 mL(H-2) min(-1)-a performance achieved without any catalyst-and the formation of NaB(OCH3)(4)as single product as identified by X-ray diffraction, Fourier transform infrared spectroscopy, and nuclear magnetic resonance. We then focused on the transformation of this product NaB(OCH3)(4)into sodium metaborate (NaBO2), via the formation of sodium tetrahydroxyborate (NaB(OH)(4)). NaB(OCH3)(4)is easily transformed in water, by hydrolysis, at 80 degrees C and for 90 minutes, into NaB(OH)(4)and 4 equiv of CH3OH. In doing so, the cycle with CH3OH is closed. Subsequently, NaB(OH)(4)is recovered and converted into NaBO(2)under heating at 500 degrees C. This reaction liberates 4 equiv of H2O, which allows to close the cycle with water. Based on these achievements, we have finally proposed a triangular recycling scheme aiming at closing the cycle with the protic reactants of the aforementioned reactions. This scheme may be used as base for implementing a closed cycle with the couple NaBH4-CH3OH.
Keywords: methanolysis; recycling; sodium borohydride; sodium metaborate; sodium tetramethoxyborate; spent fuel; AMMONIA-BORANE; NABH4 HYDROLYSIS; SUPPORT MATERIAL; BORON HYDRIDES; FT-IR; GENERATION; CATALYST; STORAGE; REGENERATION; ENERGY; Energy & Fuels; Nuclear Science & Technology